Three Solid Modifications of Ba[Ga(NH2)4]2: A Soluble Intermediate in Ammonothermal GaN Crystal Growth. Issue 5 (6th February 2017) - Hertrampf, Jan; Alt, Nicolas S. A.; Schlücker, Eberhard; Niewa, Rainer
Abstract : Ammonothermally grown GaN crystals are highly demanded as superior substrates for manufacturing high‐performance blue and white LEDs. Ba or Ba(NH2 )2 can act as effective mineralizers under ammonothermal conditions (523 K, 110–150 MPa) and lead to the formation of barium bis(tetramidogallate), Ba[Ga(NH2 )4 ]2, a new intermediate in h ‐GaN synthesis, which was obtained in three solid forms. Single crystals of all three modifications were characterized by X‐ray diffraction techniques. Like earlier characterized intermediates in ammonobasic GaN crystal growth, all forms of Ba[Ga(NH2 )4 ]2 contain isolated [Ga(NH2 )4 ] – units. Differences between the forms originate in the coordination environments of Ba, leading to various frameworks with the [Ga(NH2 )4 ] – complex ions. Raman and IR spectroscopic data are discussed. Ba[Ga(NH2 )4 ]2 in an inert gas thermally decomposes in several steps to finally yield the intermetallic compound BaGa2 . Abstract : Ba or Ba(NH2 )2 can act as effective mineralizers under ammonothermal conditions (523 K, 110–150 MPa) and lead to the formation of barium bis(tetraamidogallate), Ba[Ga(NH2 )4 ]2, a new intermediate in h ‐GaN synthesis. All forms of Ba[Ga(NH2 )4 ]2 contain the isolated complex ion [Ga(NH2 )4 ] – .